2018
DOI: 10.1038/nature25448
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain circuits that set locomotor speed and gait selection

Abstract: Summary Locomotion is a fundamental motor function common to the animal kingdom. It is executed episodically and adapted to behavioural needs including exploration, requiring slow locomotion, and escaping behaviour, necessitating faster speeds. The control of these functions originates in brainstem structures although the neuronal substrate(s) supporting them are debated. Here, we show in mice that speed/gait selection are controlled by glutamatergic excitatory neurons (GlutNs) segregated in two distinct midbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
511
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(590 citation statements)
references
References 39 publications
53
511
4
Order By: Relevance
“…In their recent work, Caggiano et al [2] and Josset et al [3] further explored the anatomical and molecular heterogeneity of the mesencephalic locomotor region, highlighting the differential role of glutamatergic and cholinergic neurons within the cuneiform and pedunculopontine nuclei. They found that glutamatergic cuneiform nucleus neurons were able to drive the full range of locomotor gaits — walk, trot, bound and gallop — and speed.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their recent work, Caggiano et al [2] and Josset et al [3] further explored the anatomical and molecular heterogeneity of the mesencephalic locomotor region, highlighting the differential role of glutamatergic and cholinergic neurons within the cuneiform and pedunculopontine nuclei. They found that glutamatergic cuneiform nucleus neurons were able to drive the full range of locomotor gaits — walk, trot, bound and gallop — and speed.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
“…Caggiano et al [2] went on to characterize the firing properties of glutamatergic neurons during locomotion at different speeds using extracellular recordings, showing that pedunculopontine nucleus neurons are more active at lower speeds, whereas cuneiform nucleus neurons are strongly recruited during fast locomotion. Further behavioral analyses have led the authors to propose a model in which the glutamatergic neurons of the cuneiform nucleus elicit fast locomotion to enable an escape response, whereas glutamatergic neurons of the pedunculopontine nucleus facilitate slow locomotor movements to favor an explorative behavior.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
See 3 more Smart Citations